(untitled) (American Journal of Engineering , Mechanics and Architecture (2993-2637), 2024)
this article discusses the current problems of organizing hydraulic engineering construction and their significance, as well as what and in what order needs to be built in accordance with the “Construction Organization Project” (COP) and detailed designs developed during construction. Stage (DDC) refers to the design associated with what technology to use, in what time frame and with what resources.